The Relationship Between Self-Esteem and Mental Health Of Adolescents - riyono, Medi; Setiyorini, Erni (Health Gate, 2025)
Mental health has serious consequences for the future of adolescents. Poor mental health affects routine activities, damages relationships, and hinders development and productivity. Adolescents with mental health problems have difficulty completing schoolwork. Various sources state that self-esteem is a predictor of mental health. This study aims to determine the relationship between self-esteem and mental health in adolescents. The research design was correlational with a cross-sectional approach. The population was 279 adolescents of Srengat junior high school in grade 8. A sample of 164 people was determined using a purposive sampling technique. The independent variable is self-esteem, and the dependent variable is mental health. Data collection used a questionnaire, which involved filling out a Google form—analysis using Spearman-Rho with a confidence value (α) of 0.05. The results showed that most respondents had high self-esteem, namely 59.1%, and almost all had good mental health, namely 87.2%. The Spearman Rho test results showed a p-value = 0.000 (> α = 0.05), r = 0.424, meaning that there is a relationship between self-esteem and mental health of adolescents at Srengat junior high school with moderate strength. This study concludes a significant relationship between self-esteem and adolescents’ mental health; the better the self-esteem, the better the mental health of adolescents. Schools and parents should pay more attention to adolescents by taking a personal approach in an effort to improve mental health by increasing adolescent self-esteem.